Transabdominal ultrasonography for confirmation of accurate percutaneous endoscopic gastrostomy tube placement: analysis of patient- and procedure-related complications - Wildner, Dane; Pfeifer, Lukas; Vitali, Francesco; Neurath, Markus; Albrecht, Heinz (Medical Ultrasonography, 2022)
Aims: Technique-related factors, patient-related factors, and localization determine the risk for complications in percutaneous endoscopic gastrostomy (PEG) tube placement. The objective of this study was to identify patient characteristics and ultrasonographic parameters after PEG tube placement concerning localization, which correlate with complications. Material and methods: Patients undergoing PEG-tube placement were examined by abdominal ultrasound after dismissal from the endoscopic recovery room. Patient demographics, PEG characteristics, ultrasonographic parameters and complications were retrospectively analyzed. Results: Of 64 enrolled patients, 59.4% were male and the mean age was 62.3 years. A significant negative correlation between complications at PEG placement and Body-Mass-Index (BMI; kg/m(2)) was observed (Spearman's Rho: -0.382; p=0.002). A low BMI <18 tended to be more frequent in the group with complication-related PEG removal compared to patients without (18.2% vs. 1.9%). Further descriptive analysis revealed that 4 patients (36.4% of N=11) with and 5 patients (9.4% of N=53) without PEG removal due to complications already had complications at the time of PEG placement. Of the patients with complications during follow-up, those with a peritoneal course (N=10) in ultrasound tended to have a lower BMI (mean +/- standard deviation: 22.5 +/- 6.5 vs. 26.8 +/- 5.9) compared to those without (N=5). In all 4 patients with a triad of follow-up complications, peritoneal course, and complications at PEG placement, the tube was removed due to complications. Conclusions: Post-PEG-placement ultrasonography can help to determine complications in specific procedure-related conditions. A low BMI was found to be a relevant predictor of PEG-related complications, substantiating the need for early intervention in potentially PEG-relevant indications.
CRIS-Team WoS Importer:2023-03-03